Absorption Kinetics of Subcutaneously Administered Ceftazidime in Hypoperfused Guinea Pigs - Tsuyoshi Ebihara, MS; Shinji Oshima, PhD; Mitsuyoshi Okita, MS; Sayumi Shiina, MS; Akio Negishi, BS; Kousuke Ohara, BS; Shigeru Ohshima, PhD; Hiroyuki Iwasaki, MD; Akira Yoneyama, MD; Eiji Kitazumi, MD; Daisuke Kobayashi, PhD (Elsevier, 2015)
Background: Pneumonia is the most common cause of death in patients with severe motor and intellectual disabilities (SMID), and intravenous ceftazidime (CAZ) is a widely used treatment for such infections. However, intravenous administration in patients with SMID may be difficult because of insufficient vascular development. Objectives: The aim of our study was to determine the feasibility of subcutaneous drug administration by mentholated warm compresses (WMCs) as an alternative delivery method for ceftazidime in patients with SMID. Methods: CAZ was subcutaneously administered to the abdominal region of naphazoline-treated hypoperfused guinea pigs, which were used as a hemodynamic model of patients with SMID. MWCs or warm compresses (WCs) were applied to the injection site to increase blood flow. We calculated the cumulative CAZ absorption over time by using the deconvolution method. Results: Application of MWCs or WCs increased blood flow at the administration site and increased CAZ plasma levels. Application of MWCs or WCs after subcutaneous CAZ injection led to higher CAZ plasma levels than the mutant prevention concentration for a longer period than was observed for CAZ administration without the application of MWCs or WCs. Conclusions: The application of MWCs or WCs enhanced subcutaneous CAZ absorption by increasing blood flow. MWCs and WCs are considered to be safe and routine methods to induce defecation after surgery on the digestive system; thus, the combination of these methods and subcutaneous CAZ administration is a potential method for treating pneumonia in patients with SMID.